Prognostication using SpO2/FiO2 in invasively ventilated ICU patients with ARDS due to COVID-19 – Insights from the PRoVENT-COVID study - Roozeman, J-P; Mazzinari, G; Serpa Neto, A; Hollmann, MW; Paulus, F; Schultz, M; Pisani, L (Elsevier, 2021)
Background: The SpO2/FiO2 is a useful oxygenation parameter with prognostic capacity in patients with ARDS. We investigated the prognostic capacity of SpO2/FiO2 for mortality in patients with ARDS due to COVID–19.